Theoretical and methodological challenges of studying the impartiality of justice evaluations - Kinga Wysieńska-Di Carlo; Zbigniew Karpiński (Ask, 2022)
We extend Jasso and colleagues’ (Jasso, Shelly, Webster 2019) research into expressiveness and impartiality of justice evaluations, both methodologically and substantively. Substantively, using the concepts developed within the distributive justice framework, we bridge the justice evaluation function with theories of reward expectations and social identity to explain variation in expressiveness across situations. We hypothesize that such variation is systematically linked to the degree of (dis)similarity between the evaluator and the person being evaluated. Methodologically, we propose a novel analytical strategy to estimate expressiveness and to test hypotheses about its variability based on a series of mixed-effects models with random slopes and random intercepts. To verify our hypotheses, we use data from a recent vignette survey carried out in Poland on a nationwide sample. Our results are more consistent with reward expectation theory than with social identity theory.